Analysis of the genetic diversity among accessions of cotton germplasm collection - Carvalho, Luiz Paulo de; Lanza, Marcelo Abreu; Fallieri, Joel; Santos, José Wellingthon dos (Pesquisa Agropecuaria Brasileira, 2003)
The knowledge of the genetic diversity among groups of parents is important to plant breeding mainly in the identification of hybrid combinations that show more heterozigosity and higher heterotic effect, and in the recovering of greater genotypes in segregating generations. The predictive methods of diversity have been used considerably because they discard the obtainment of hybrid combinations between parents. They often use a measure of similarity to evaluate the diversity, such as the euclidean distance. In this work 221 accessions of germplasm collection belonging to Epamig were evaluated using the euclidean distance and later grouping the accessions to get an alternative criterion to choose parents for hybridization. Eleven morphological and fiber traits were considered. A great diversity among the 221 accessions was observed and they were clustered in 10 groups. The largest euclidean distance mean obtained (4.36) was between the S 8186 and T-295-1-1 accessions and the smallest (0.25) between the TX CACES 1-81 and TX CDPS 177 accessions.